THE IMPORTANCE AND FULFILLMENT OF THE SUCCESS CRITERIA IN PROJECTS IMPLEMENTED BY SMALL AND MEDIUM-SIZED ENTERPRISES - Csiszárik-Kocsir, A; Varga, János (PEOPLE: International Journal of Social Sciences, 2019)
Projects have become key players in national economies today. Projects are concrete manifestations of investments, there are no investments without projects, and without them the economy cannot grow substantially. The investments are so important in national economies as well. Investments are the main components of the gross domestic product, so they are the promoters of growth. However, projects are unsuccessful in many cases, because they aren’t prepared in time; don’t achieve the required performance they expect from them. A common cause of project failure is a poor planning process, budgetary problems, the missed investment calculations, or the omission of sustainability, relevance, and feasibility. These expectations are expressed in every project management course, all of the literature dealing with the projects, but the project actors don’t give the required relevance to them. The success of the project is contributed by many factors, among which are supporting, and hindering ones. Based on a classical project triangle, the key factors lead to the successful project are time, cost and effectiveness, these are the main project baselines. The Hungarian surveys show, that nearly three-quarters of the projects fail, in which the planning, financing and management also play a role. The aim of this study is to show the Hungarian SME’s opinion about the success factors, to pay attention to the critical areas in the project management as well.